Understanding drivers of self-service technologies (SSTs) satisfaction and marketing bottom lines: Evidence from Nigeria - Chidera C. Ugwuanyi; Chukwunonso Oraedu; Chuka Uzoma Ifediora; Ernest Emeka Izogo; Simplice Asongu; Ikechukwu J. Attamah (African Governance and Development Institute (AGDI), 2022)
Whilst self-service technologies (SSTs) are novel and evolving, they have rapidly grown popular across various retail service settings. Having been introduced into the Nigerian banking space, the level of customers' satisfaction from the system is still unknown given that it has disrupted the initial service setup customers were used to. Utilising two theoretical perspectives, this study examined what drives customers' satisfaction with banks' SST and further assesses their influence on different marketing bottom lines. The study employed a quantitative approach to sampling 310 banks' SST users within a popular university in Eastern Nigeria. Using the PLS-SEM technique, the study found that the perceived ease of use and perceived control are strong drivers of SST satisfaction and other marketing bottom lines. Surprisingly, perceived usefulness was found not to influence SST satisfaction, and therefore present a unique result in this context. Based on the foregoing, theoretical and managerial implications were provided.
Keywords: 330; Customer behaviour; Customer satisfaction; Technology Acceptance Model; Selfservice technologies (SSTs); Stimulus-Response-Organism (S-O-R) Theory; Nigeria